Forgotten Heroes: Family Planning Cadres in Politics of Sexuality in Surakarta (1973-1998) - Adi Putra Surya Wardhana (Yayasan Jurnal Perempuan, 2017)
This paper explains the role of cadres in family planning program (KB) at Surakarta. Family Planning program is the priority of New Order Government to reduce the rapid population growth rate. The program was initially difficult to be accepted by the community.This is due to the values and norms of society that oppose birth restrictions. Therefore the government uses society approarch strategy by forming family planning cadres. This study uses historical method consist of heuristic, source critique, interpretation, and historiography. This research shows that family planning is a politics of sexuality constructed by the government. FP cadres became discourse knowledge agents of the New Order to achieve legitimacy. However, FP cadres consider that their activity is a service to the state. Their existence shows that women have great power in the social sphere amid patriarchal hegemony in Javanese society.